UJI COBA PENANGKAPAN MENGGUNAKAN AYUNAN DENGAN BENTUK YANG BERBEDA (EXPERIMENTAL FISHING USING AYUNAN WITH DIFFERENT FORMS) - Irhamsyah Irhamsyah (Fish Scientiae, 2019)
Ayunan is the trap most widely used by public Sungai Batang Village, inaddition to the unique shape of this tool also has an extensive capacity toaccommodate good catches of shrimp and fish species. In addition to the village ofSungai Batang, at the Hulu Sungai region there is also the ayunan that looks differentfrom contained in Sungai Batang Village.This study aims to (1) know the difference between shrimp of catch amorayunan and box ayunan, and (2) to determine the catch other than shrimp. Theresults of research, treatment A (amor ayunan) shrimp catches as many as 1464 ,with a total weight of 9100 grams. Treatment B (box ayunan), shrimp catches asmany as 1443 , with a total weight of 7730 grams. Type of main haul shrimp(Macrobrachium rosenbergii de Man) and Freshwater Shrimp (Palaemon sp), with bycatches are Lundu (Mystus gulio) with a total of 18 and total weight of 215 grams,sapu-sapu (Hypostomus plecostomus ) 2 , weighing a total of 560 grams, Puyau(Osteochilus hasselti) 3 , weighing a total of 35 grams, telan (Macrognathusaculeatus) 2 , weighing 810 grams.Bamboo and rattan as materials to make the ayunan has a weaknessbecause odor (smell) is not good (bangai) and therefore contributes to the catch. Toovercome this weakness it is advisable to replace the wire with the basic material.